Development of E-Learning Materials Assisted by Augmented Reality on the Material of the Form of Matter and its Changes to Improve Learning Outcomes of Elementary School Students - Fatza Hermayanti; Novi Setyasto (Postgraduate, University of Mataram, 2025)
This study aims to develop, test the feasibility of effectiveness, and practicality of E-learning materials assisted by Augmented Reality to improve cognitive learning outcomes of fourth grade students of Kemijen 02 Elementary School, Semarang City. This type of research is development research (R&D) using the ADDIE model. The subjects of the study were 52 fourth grade students of Elementary School. Data collection techniques include non-test and test. Data analysis techniques use t-test, and N-Gain test. The results of the study indicate that the development of E-learning materials assisted by Augmented Reality (AR) includes covers, instructions for use, concept maps, learning competencies, materials, videos, Augmented Reality (AR). From the results of the feasibility test, the percentage of assessment was obtained, namely the validator of language experts 94.40%, media experts 91.18%, and material experts 91.40% with the category